An experimental investigation of the impact of aquatic weeds trash racks on water surface profile in open channels. Issue 1 (2nd January 2019) - Salah Abd Elmoaty, Mohamed
ABSTRACT: A considerable quantity of weeds is drafted with flow due to maintenance activities and moving vessels causing serious problem to hydraulic structures and hydropower plants along open channels. Aquatic weed trash screens are normally constructed upstream hydraulic structures to control the drafted weeds and preventing them from passing through the hydraulic structures. The effect of the presence of accumulated aquatic weed upstream trash racks on water surface profile is the main disadvantage of trash racks. In this research, the effect of the presence of trash rack and the accumulated weeds upstream it with different densities on water surface profile is studied experimentally. Ninety runs were applied in the hydraulic lab of Channel Maintenance Research Institute. Equations relating different hydraulic parameters and accumulated weed density to the water surface profile were established. It was concluded that accumulated weed depth is the most effective parameter on heading up, while the blocked area of trash rack screen and extension length of weed upstream the barrier are the most effective parameters on head loss.